1991
DOI: 10.1002/ijc.2910480411
|View full text |Cite
|
Sign up to set email alerts
|

Intake of foods and nutrients and cancer of the exocrine pancreas: A population‐based case‐control study in the Netherlands

Abstract: During 1984-88 a population-based case-control study was carried out in the Netherlands in collaboration with the International Agency for Research on Cancer in order to investigate the role of diet in exocrine pancreatic carcinoma. A semi-quantitative food-frequency questionnaire was used to comprehensively assess usual diet about 1 year prior to diagnosis of 164 cases or interview of 480 controls. More than half of the cases were directly interviewed. After controlling for age, gender, response status, life-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
105
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 31 publications
1
105
0
3
Order By: Relevance
“…Positive associations have been reported for the following: daily meat consumption (29); total meat, liver, ham, and sausages (30); red meat and salted/ smoked meat (31); beef and bacon (32); pork and beef (33,34); pork and fish, but not beef (35); beef, chicken, and pork (36), and fat (37)(38)(39). Null, inverse, and inconsistent associations have also been reported (40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Positive associations have been reported for the following: daily meat consumption (29); total meat, liver, ham, and sausages (30); red meat and salted/ smoked meat (31); beef and bacon (32); pork and beef (33,34); pork and fish, but not beef (35); beef, chicken, and pork (36), and fat (37)(38)(39). Null, inverse, and inconsistent associations have also been reported (40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in agreement with those of five previous case -control studies that reported statistically significant or borderline decreased risks of pancreatic cancer with higher saturated fat intake, with a relative risk of 0.3 (95% CI 0.1 -0.8), 0.3 (95% CI 0.1 -1.0), 0.2 (95% CI 0.1 -0.2), and 0.9 (P-trend ¼ 0.028; for men) for intakes in the highest as compared to the lowest quartiles (Baghurst et al, 1991;Bueno de Mesquita et al, 1991;Zatonski et al, 1991;Silverman et al, 1998), respectively. A large collaborative population-based case -control of pancreatic cancer comprising 802 cases from five countries in the Surveillance of Environmental Aspects Related to Cancers in Humans (SEARCH) Study found a nonsignificant reduced risk, with an overall OR of 0.8 (95% CI 0.6 -1.2) for the highest quartile of saturated fat intake (Howe et al, 1992), with significant inverse associations reported in two study centres (Howe and Burch, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The association between meat intake and pancreatic cancer has been examined in both case control and cohort (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) studies with positive (2-7, 9-12, 22-27), inverse (13)(14)(15)28), and null (4, 5, 8, 14-21, 29, 32) associations reported for both study designs. The inconsistent results among case-control studies may partly be due to retrospective ascertainment of diet, which, given the rapid fatality of pancreatic cancer, may be fraught with biases, such as recall and proxy, and reverse causation.…”
Section: Introductionmentioning
confidence: 99%